Oto–Acoustic Emission and Auditory Brainstem Response Profile in Children with Speech Delay at Dr. Hasan Sadikin General Hospital Bandung - Liani Mulasari Gunawan; Wijana Wijana; Yuni S Pratiwi (Althea Medical Journal, 2016)
Background: Language and speech delay are the most common developmental disorders found in children. Hearing loss is the most common cause of speech delay among children. Hearing loss can be detected by subjective and objective examinations. Oto–acoustic emission (OAE) and auditory brainstem response (ABR) are objective electrophysiological examination with 100% sensitivity and 99% specificity. This study was aimed to describe OAE and ABR profile in children with speech delay at Dr. Hasan Sadikin General Hospital BandungMethods: This study was conducted in 2014 used the descriptive cross–sectional design with a total sampling of 333 medical records of children diagnosed with speech delay with inclusion criteria patients aged 1–5 years at the Hearing Disorders Clinic of Otorhinolaryngology–Head and Neck Surgery Policlinic at Dr. Hasan Sadikin General Hospital Bandung during the period of 2011–2012.Results: Out of all of the samples, there were 176 boys (52.9%) and 157 girls (47.1%). Most of children aged 24–35 months. Eighty children (24%) with normal hearing and 253 children (76%) with hearing loss. Hearing loss with Sensorineural hearing loss (SNHL) type most occured at the profound degree with 244 cases.Conclusions: Hearing loss is the most common cause of speech delay in children. Speech delay can be prevented by conducting the OAE and ABR examinations as early as possible. [AMJ.2016;3(2):265–8]  DOI: 10.15850/amj.v3n2.771